2018
DOI: 10.1158/1538-7445.sabcs17-p6-14-04
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P6-14-04: Is fat mass more effective than body mass index (BMI) to predict toxicity in early breast cancer patients treated with doxorubicin and cyclophosphamide?

Abstract: Patients and Methods:We performed a retrospective cohort study of 207 operated breast cancer women treated with doxorubicin (60 mg/m2) and cyclophosphamide (600 mg/m2) for adjuvant setting between 2007 and 2016. Patients' demographic features, toxicities, fat mass, body mass index (BMI) and body surface area (BSA) were evaluated in their charts. Patients were evaluated according to fat mass (high ≥35% vs. low <35%), BMI (obese ≥30 kg/m2 vs. nonobese <30 kg/m2), and BSA (≥1.73 vs. <1.73) le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It is well known that this refers mainly to the increase in body fat [8]. Numerous studies have shown that excess body fat and its specific depositing, depending on gender, significantly increases the risk of ischemic heart disease, diabetes, hypertension, or various forms of cancer [9,10,11,12,13,14]. The effects of an imbalance in the body of individual body components affects people of all ages.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that this refers mainly to the increase in body fat [8]. Numerous studies have shown that excess body fat and its specific depositing, depending on gender, significantly increases the risk of ischemic heart disease, diabetes, hypertension, or various forms of cancer [9,10,11,12,13,14]. The effects of an imbalance in the body of individual body components affects people of all ages.…”
Section: Introductionmentioning
confidence: 99%
“…J. Sport Tourism 2022, 29 (2), [11][12][13][14][15][16][17] in any case, and the average was approximately 65% of the maximum heart rate in test 1 and approximately 70% in test 2, which roughly corresponds to the oxygen consumption at 55 and 60% VO2max, respectively. Although after both tests the applied effort caused an increase in the concentration of lactic acid (LA), this parameter did not exceed the lactate threshold (4 mmol/l) in most of the examined women (85% of the group).…”
Section: Discussionmentioning
confidence: 78%
“…J. Sport Tourism 2022, 29 (2), [11][12][13][14][15][16][17] each participant. Only women who did not show any abnormalities of their menstrual cycle were qualified to take the measurements.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation